Observational analysis of the predictability of mesoscale convective systems - Jirak, Israel L., author; Cotton, William R., advisor; Rutledge, Steven A., committee member; Johnson, Richard H., committee member; Ramírez, Jorge A., committee member (Colorado State University. Libraries, 2005)
Mesoscale convective systems (MCSs) have a large influence on the weather over the central United States during the warm season by generating essential rainfall and severe weather. To gain insight into the predictability of these systems, the precursor environment of several hundred MCSs were thoroughly studied across the U.S. during the warm seasons of 1996-98. Surface analyses were used to identify triggering mechanisms for each system, and North American Regional Reanalyses (NARR) were used to examine dozens of parameters prior to MCS development. Statistical and composite analyses of these parameters were performed to extract valuable information about the environments in which MCSs form. Similarly, environments that are unable to support organized convective systems were also carefully investigated for comparison with MCS precursor environments. The analysis of these distinct environmental conditions led to the discovery of significant differences between environments that support MCS development and those that do not support convective organization. MCSs were most commonly initiated by frontal boundaries; however, such features that enhance convective initiation are often not sufficient for MCS development, as the environment needs to lend additional support for the development and organization of long-lived convective systems. Low-level warm air advection, low-level vertical wind shear, and convective instability were found to be the most important parameters in determining whether concentrated convection would undergo upscale growth into a MCS. Based on these results, an index was developed for use in forecasting MCSs. The MCS index is comprised of conditional terms to ensure that the index is only defined in regions where convective initiation and development are possible. The MCS index assigns a likelihood of MCS development based on three terms: 700 mb temperature advection, 0-3 km vertical wind shear, and the lifted index (LI). Each of these parameters promotes convective development and organization through the enhancement of vertical lifting. An analysis of the MCS index showed that it exhibits similar diurnal, episodic, and seasonal characteristics to MCSs. In addition, an objective evaluation of the MCS index revealed that it possesses significant skill in forecasting MCSs, especially given that convective initiation has occurred, offering the possibility of usefulness in operational forecasting.
Keywords: atmosphere